Analisis kinerja keuangan menggunakan metode economic value added dan market value added pada perusahaan sub sektor perdagangan ritel barang primer yang terdaftar di Bursa Efek Indonesia - Ramopolii, Gemma Milani; Runtu, Treesje; Latjandu, Lady Diana (Yayasan Widyantara Nawasena Raharja, 2024)
Financial performance analysis is a method of verifying that a company has properly and correctly applied the principles of financial implementation. This study will determine the financial performance of primary goods retail trade sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period using the economic value added and market value added methods. This research is qualitative descriptive. The research was conducted on retail trading companies of primary goods listed on the IDX during the research period and has published financial statements during the research period. The data was obtained by the documentation method. The results of the research from the five primary goods retail trading companies studied showed a volatile but positive EVA result (EVA>0), while MVA results were consistently positive (MVA>0). Only DAYA and RANC companies in 2019 and MIDI companies in 2023 had a negative MVA (MVA<0).